Relationship of Aboriginal family wellbeing to social and cultural determinants, Central Australia: 'Waltja tjutangku nyakunytjaku'. Issue 4 (10th November 2022) - Wright, Alyson; Davis, Vanessa Napaltjarri; Brinckley, Makayla-May; Lovett, Raymond; Thandrayen, Joanne; Yap, Mandy; Sanders, William; Banks, Emily
Abstract : Objective: The objective of this study was to apply a strength-based approach to examine the relation of cultural and social determinants to high family functioning for Aboriginal people in Central Australia. Design: Cross-sectional study involving a quantitative analysis of survey data. Prevalence rate ratios (PRs) and 95% CIs were calculated from binomial regressions, adjusted for gender and age. Qualitative data from workshops with Aboriginal leaders in Central Australia supported the interpretation of the research findings. Participants: The study involved 639 Aboriginal people in Central Australia who participated in the Mayi Kuwayu Study. Result: Overall, 57.9% (370/639) of participants reported high/very high family functioning, 16.9% (108/639) reported moderate and 13.3% (85/639) reported low. The adjusted prevalence of family functioning was similar across gender, age groups and household sizes. Family functioning was associated with lower family financial status (aPR=0.74, 95% CI=0.60 to 0.91) and receiving welfare (0.88, 0.77 to 1.00). Family functioning was greater with high community cohesion (2.72, 1.68 to 4.39), high individual agency in community (2.15, 1.63 to 2.85); having an Aboriginal language as a first language (1.20, 1.04 to 1.37); speaking your Aboriginal language a lot (1.37, 1.12 to 1.68); high exposure to cultural practice and knowledge (1.45, 1.28 to 1.65); and multigenerational or extended family households (1.19, 1.02 to 1.38). Conclusion: High family functioning is a strength in Central Australia and is intrinsically connected with culture. Healthcare providers and programmes that build on the foundations of culture and family are an important approach to improving wellbeing.